2012
DOI: 10.1097/prs.0b013e31825dbf73
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine, Norepinephrine, Dobutamine, and Dopexamine Effects on Free Flap Skin Blood Flow

Abstract: Both dobutamine and norepinephrine had beneficial effects on flap skin blood flow. The maximal improvement in flow occurred with norepinephrine, making it the optimal pressor to use in patients with hypotension after free flap surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 5 publications
4
60
1
1
Order By: Relevance
“…36,37 Prospective studies comparing epinephrine, norepinephrine, dobutamine, and dopexamine postoperatively demonstrated that both dobutamine and norepinephrine improved free flap skin blood flow, with norepinephrine yielding the greatest improvement. 34,35 In contrast, dopexamine and epinephrine decreased flap flow. 34…”
Section: Vasopressorsmentioning
confidence: 96%
“…36,37 Prospective studies comparing epinephrine, norepinephrine, dobutamine, and dopexamine postoperatively demonstrated that both dobutamine and norepinephrine improved free flap skin blood flow, with norepinephrine yielding the greatest improvement. 34,35 In contrast, dopexamine and epinephrine decreased flap flow. 34…”
Section: Vasopressorsmentioning
confidence: 96%
“…This study showed that both dobutamine and norepinephrine had beneficial effects on flap skin blood flow, and that the maximal improvement in flow occurred with norepinephrine (Level V Evidence). 137 Dobutamine had little vasoconstrictive effect, increasing flow in the flap and control without changing blood pressure. The vasospastic effects of norepinephrine were overcome by the rise in blood pressure up to a dose of 0.15 μg/kg/ minute optimal pressor to use in patients with hypotension after free flap surgery.…”
Section: Anesthetic Considerationsmentioning
confidence: 96%
“…The thought is that an attenuated pressor response occurs after surgical sympathectomy, which occurs during vessel dissection [29]. Dobutamine was found to improve flap flow and both dobutamine and norepinephrine improved free flap skin blood flow [30]. Phenylephrine and epinephrine both decreased flap flow [31].…”
Section: Special Considerations Vasoactive Medicationsmentioning
confidence: 99%